Business Model Canvas : Easy Sdn Bhd / Nurul Anies Suraya Young Rockie - Young Rockie, Nurul Anies Suraya (2020)
The product is targeted on household which is defined by a group of family who live together. Our customer is expected to be a household owners since the Space-Saving Plastic Bag Storage Box is commonly used in home to store used plastic bags